Influence of storage under controlled temperature the physical characteristics of jujube fruits (Ziziphus joazeiro Mart.) (Research, Society and Development, 2020)
Ziziphus joazeiro Mart. is a typical species from the Northeast of Brazil, which produces fruits rich in ascorbic acid and a high concentration of phenolic compounds, requiring research on the post-harvest storage of its fruits, in order to intensify its consumption, industrialization and commercialization. Thus, the objective was to evaluate the influence of storage under controlled temperature on the physical characteristics of juazeiro fruits. The ripe fruits were harvested from plants located at the Center for Science and Agrifood Technology, Federal University of Campina Grande, Campus Pombal/PB. After selection, classification, removal of dirt, removal of the peduncle and packaging, the fruits were subjected to storage at controlled temperature (24.5 ± 0.5 °C and 33.5 ± 0.5% RH), for 4 days. On all storage days, analysis of physical characteristics (fresh mass, loss of fresh mass, longitudinal and transverse lengths, thickness, yield, firmness and humidity) was performed. The results indicate that storage affected most of the characteristics studied in this research and when compared to previous studies, it is clear that the attack of the pest on juazeiros, at the time of this work, affected both flowering and fruit development.